Prevalência de microdeleções nas regiões AZFA, AZFB e AZFC do cromossomo Y em indivíduos com Oligozoospermia ou Azoospermia em Mato Grosso - Santos, Gleice Cristina dos (2011)
to establish the prevalence of chromossomal alterations and microdeletions of the chromosome Y in individuals with oligozoospermia or azoospermia in the Mato Grosso state. Material and methods: 95 patients were selected.The study period was between March 14, 2009 and June 14, 2011. A patient was excluded by not having fulfill a semen. This way, the sample was established in 94 patients. The methodology used for chromosomal analysis was based on the lymphocyte culture technique, proposed by Moorhead et al (1960), and DNA samples were extracted using the method described by Lahiri and Nurnberg (1991). The investigation of microdeletion was performed by PCR technique. Results: In the cytogenetic evaluation of patients, five (5.4%) had altered karyotype, one with severe oligozoospermia had karyotype 46,XY, 8p+. Another patient with azoospermia had karyotype 46,XY,t(7; 1)(qter-p35). The third had mild oligozoospermia with karyotype 46, XY,del(q). In addition, two other patients had azoospermia karyotype 47, XXY, consistent with the Klinefelter syndrome. Y chromosome microdeletion was detected only in the AZFc region in one patient (1 / 94, 1.1%) with azoospermia. Conclusion: We conclude that all patients seeking treatment for infertility with low sperm count should be tested for analysis microdeletions and cytogenetic. The correct diagnosis allows the physician to refer the patient to most appropriate medical treatment and provide a more accurate diagnosis of infertility.